The Spiritual Aspect of Female Students’ Well-being during the Pandemic - Izabella Maria Łukasik (Lubelski Rocznik Pedagogiczny, 2022)
Introduction: The epidemic is a difficult time of personal struggles with fears, weaknesses and illness. One of the factors that influences people’s overall well-being is what can be called spirituality – understood as an individual’s religiosity or search for meaning of life, not necessarily in the transcendental sense. Research Aim: To try to determine whether it is possible to find a confirmation for the significance of faith for spiritual well-being in time of self-denial as described by Delsol. Method: A group of respondents (58 part-time female students) gave their online assessments of their physical, mental, social and spiritual well-being. Their responses regarding spiritual well-being were analysed using the CLARIN: Summarize (ReSpa) tools. The obtained corpus was described in terms of emotionality, drawing on Plutschik’s theory. A number of responses by the surveyed students were provided as examples. Results: When describing their spiritual well-being, the surveyed students were more likely to express positive than negative emotions. In their responses, they mentioned searching for spiritual support and talked about happiness. Their responses on spiritual well-being focused on two categories – religiousness and the meaning of life – not necessarily invoking the presence of God. Conclusions: The study proved that faith is a factor in spiritual well-being in “time of self-denial”. Praying can fulfil a therapeutic function in and of itself. It should be stressed that the newly found spirituality is closely linked to the world as shaped by the media, with the sensationalistic communications about the epidemic-related health issues, not always proven to be true, contributing to poor well-being and depression.